The Nouns of the Media Discourse on Brexit in the Spanish Business Press: Study of Information Bias and Semantic Prosody - Ramos Ruiz, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The information in the press may reflect a certain informative bias in the published texts. Therefore, the objective of this paper is to analyze what was the discursive construction that the Spanish economic press made of the term ‘Brexit’. To do this, a lexical-semantic analysis, based on the study of the semantic prosody of the nouns co-occurring with ‘Brexit’, was carried out. The results shown that the Spanish economic press present a mainly neutral editorial stance when reporting on Brexit.